Trabalho, educação e produção associada : experiências de jovens e mulheres do assentamento Roseli Nunes em Mirassol D'Oeste – MT - Azevedo, Eva Emilia Freire do Nascimento (2020)
This work is the result of a PhD research developed from the Study and Research Group on Labor and Education (GEPTE), in the line “Social Movements, Politics and Popular Education”, of the Institute of Education (IE) of the Graduate Program in Education (PPGE), of the Federal University of Mato Grosso (UFMT). This study had as general objective to know what the youth and women of Roseli Nunes Settlement learn, who collaborate to produce their existence, as well as what they have to teach about economic-social relations and how they experience a form of work articulated to a broader movement in defense of another society project. The research was carried out at Roseli Nunes Settlement (Mirasol D’Oeste- MT), conquered by an intense process of struggle of the Landless Rural workers Movement (MST), in which today more than 331 families live, mostly producing existence from agriculture, especially agro-ecological one. It is a study based on dialectical historical materialism and that used elements of participant research, as it has also made use of interviews, round table discussions, participant observation and records in field diary. Among the results found the following ones stand out: the learnings originating from the members/self-management work; the challenges of producing agroecologically in the midst of the agribusiness advance and investments; the objective conditions for the production disposal and commercialization; the non-continuity of the young people groups. It is also identified that this youth and women located in this empirical field have struggles and resistances that materialize in the daily life of their stocks, when they produce without pesticides, when they question paid work, when they leave the exclusivity of the domestic space, when they continue their studies, when they criticize agribusiness, by thinking about strategies against mining – the latter ones considered increasingly present threats. It is concluded that the experiences of associated production, experienced by the youth and women of Roseli Nunes settlement, reaffirm work as an educational principle, contributing to the strengthening of their relationship with the land, which suggests an alternative production of existence (material and immaterial) to the capitalist mode of production.